Decision Support System Recipient In the House Surgery Department of Housing and Settlement Region Deli Serdang Using TOPSIS Method - Irwanda Prayogi; Bosker Sinaga (Information Technology and Science (ITScience), 2020)
The Inappropriate Home Assistance Program (PRTLH) or Home Renovation is assistance provided by the government to people who are Unable to reduce the economic burden. This assistance can be Obtained if the prospective beneficiary meets the specified criteria and conditions. This research is motivated by the house renovation assistance to the community is still subjective, less objective in the selection of the data and the weakness of the system used today. Therefore to help in the selection, a system for decision support was made in Determining the prospective recipient of house surgery assistance using the web-based TOPSIS method using a MySQL database, so that it can help smooth the evaluation process in the selection of subsequent home surgery recipients.